2008
DOI: 10.1099/vir.0.83385-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of picornavirus RNA replication within infected cells

Abstract: Replication of many picornaviruses is inhibited by low concentrations of guanidine. Guanidine-resistant mutants are readily isolated and the mutations map to the coding region for the 2C protein. Using in vitro replication assays it has been determined previously that guanidine blocks the initiation of negative-strand synthesis. We have now examined the dynamics of RNA replication, measured by quantitative RT-PCR, within cells infected with either swine vesicular disease virus (an enterovirus) or foot-and-mout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Positions 55 and 85 have not been identified as related to resistance to guanidine in FMDV [47], [48] and therefore, from the data presently available no connection between 2C positions 55 and 85 and FMDV replication is apparent. It cannot be excluded that the established role of 2C in cellular membrane rearrangements during picornaviral infection [27][31] might be connected with its effect in virus release and cytopathology.…”
Section: Discussionmentioning
confidence: 85%
“…Positions 55 and 85 have not been identified as related to resistance to guanidine in FMDV [47], [48] and therefore, from the data presently available no connection between 2C positions 55 and 85 and FMDV replication is apparent. It cannot be excluded that the established role of 2C in cellular membrane rearrangements during picornaviral infection [27][31] might be connected with its effect in virus release and cytopathology.…”
Section: Discussionmentioning
confidence: 85%
“…Guanidine resistance in picornaviruses is associated with the development of point mutations in coding region 2C (16,21,23,24), including HEV71 (22). After 13 passages in RD cells in the presence of 400 M ribavirin, we showed that the G64R and G64T virus populations grew poorly in the presence of 0.5 mM guanidine relative to growth of the G64N and parental virus populations.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, no mutations were found in the 2C coding regions of any of the plaque-purified G64R and G64T mutant populations at RD passage 1 or 13 ( Table 2). It is interesting to note that the M175K, K185R, E272K, R293K, and K298N mutations in coding region 2C have not been shown to confer guanidine resistance upon HEV71 (1) or upon other picornaviruses (16,(21)(22)(23)(24).…”
Section: Hev71 3d Mutants With High Replication Fidelitymentioning
confidence: 99%
“…Mutants of the virus which become resistant to this inhibitor have mutations within the 2C coding region. [27][28][29] Recent studies have shown that the FMDV 2C protein is a member of the AAA+ family of proteins and forms a hexameric structure. 30 The P3 region is processed to 3A, three different forms of 3B (3B 1 , 3B 2 Belsham and Bøtner FMDVs due to the presence of nucleotide mismatches within the region targeted by the primers and probes.…”
Section: Detection Of Fmdv Rnamentioning
confidence: 99%